A lithium niobium titanium negative electrode-lithium manganese iron phosphate positive electrode lithium ion battery

By using bi-shell lithium niobium titanium-titanium phosphate composite hollow microspheres as the negative electrode material of lithium-ion batteries, the existing niobium titanium oxide negative electrode materials have solved the problem of lower specific capacity and poor rate performance during high current charging and discharge, and the improvement of battery rate performance and cycle performance has been achieved.

CN115377377BActive Publication Date: 2025-03-18HUZHOU YONGXING LITHIUM BATTERY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210937662.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-05
Publication Date
2025-03-18
Estimated Expiration
2042-08-05

AI Technical Summary

Technical Problem

The existing niobium titanium oxide negative electrode materials drop faster during high current charging and discharge, and have poor rate performance, which limits their application.

Method used

SiO2@lithium niobium titanium phosphate composite hollow microspheres were used as the negative electrode material, and SiO2@lithium niobium titanium phosphate was coated as the core layer by layer, and SiO2@LATP microspheres were coated with layers of SiO2@lithium niobium titanium titanium titanium titanium phosphate was prepared by calcining and removing the template layer, and finally bicanal hollow microspheres were formed under carbon coating of glucose.

Benefits of technology

It significantly improves the electronic conductivity and ionic conductivity of the negative electrode material, improves the rate performance of the battery and the cycle performance at high magnifications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115377377B_ABST
    Figure CN115377377B_ABST
Patent Text Reader

Abstract

The invention discloses a lithium niobium titanium negative electrode-lithium iron manganese phosphate positive electrode lithium ion battery, comprising a positive electrode, a negative electrode and an electrolyte; the active material in the positive electrode is lithium iron manganese phosphate; the active material in the negative electrode is a double-shell lithium niobium titanium-lithium aluminum titanium phosphate composite hollow microsphere, and the preparation steps are: preparation of monodisperse SiO2 microspheres; preparation of SiO2@lithium niobium titanium microspheres; preparation of SiO2@lithium niobium titanium@SiO2 microspheres; preparation of SiO2@lithium niobium titanium@SiO2@LATP microspheres; primary calcination; template removal; carbon coating. The invention adopts double-shell lithium niobium titanium-lithium aluminum titanium phosphate composite hollow microspheres as negative electrode materials, which can significantly improve the electronic conductivity and ionic conductivity of the negative electrode materials, improve the rate performance of the battery and the cycle performance at high rates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium niobium titanium negative electrode-lithium manganese iron phosphate positive electrode lithium ion battery. Background Art

[0002] Lithium-ion batteries have the characteristics of high energy density, long cycle life, no memory effect, and no pollution to the environment. They have been widely used in portable electronic devices and electric vehicles. At present, the most widely used negative electrode material for commercial lithium-ion batteries is graphite. However, during the charging and discharging process, the graphite negative electrode has a lower voltage platform. During the lithium insertion and extraction process, lithium dendrites are easily formed on the negative electrode surface, which will puncture the battery separator, thus causing serious safety hazards such as short circuit. Safety issues are the key issues that lithium-ion batteries need to solve urgently.

[0003] Embedded transition metal oxides (niobium-based and titanium-based compounds) have small volume changes during the process of lithium insertion and extraction, high theoretical specific capacity, high working safety, stable cycles, high content in nature, and are environmentally friendly. They are a type of lithium-ion battery negative electrode material with great application prospects. Among them, niobium titanium oxide (NTO) negative electrode material has a narrow band gap compared to traditional titanium dioxide and niobium oxide negative electrode materials, and is expected to have better electrochemical performance.

[0004] However, niobium titanium oxide has problems such as low electronic conductivity and lithium ion mobility, which causes its specific capacity to drop rapidly during high current charging and discharging, and its rate performance is poor, limiting its application. Summary of the invention

[0005] The present invention aims to overcome the problem in the prior art that the specific capacity of lithium ion batteries with niobium titanium oxide negative electrodes decreases rapidly during high current charging and discharging and the rate performance is poor. A lithium niobium titanium negative electrode-lithium iron manganese phosphate positive electrode lithium ion battery is provided, which adopts double-shell lithium niobium titanium-lithium aluminum titanium phosphate composite hollow microspheres as the negative electrode material, which can significantly improve the electronic conductivity and ionic conductivity of the negative electrode material, and improve the rate performance of the battery and the cycle performance at high rates.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A lithium niobium titanium negative electrode-lithium iron manganese phosphate positive electrode lithium ion battery, comprising a positive electrode, a negative electrode and an electrolyte; the active material in the positive electrode is lithium iron manganese phosphate; the active material in the negative electrode is double-shell lithium niobium titanium-lithium aluminum titanium phosphate composite hollow microspheres, and the preparation method thereof comprises the following steps:

[0008] (1) Preparation of monodisperse SiO2 microspheres: under stirring, an anhydrous ethanol solution of ethyl orthosilicate is added dropwise to an anhydrous ethanol solution of ammonia water, and the reaction is stirred for 1 to 2 hours, and the product is separated to obtain monodisperse SiO2 microspheres;

[0009] (2) Preparation of SiO2@lithium niobium titanium microspheres: Nb2O5 was dissolved in hydrofluoric acid, and then citric acid was added, and then ammonia water was added to adjust the pH to 4-6 to obtain solution A; LiNO3 and tetrabutyl titanate were added to the citric acid solution, and after dissolving, ammonia water was added to adjust the pH to 4-6 to obtain solution B; monodisperse SiO2 microspheres were added to solution B, and stearic acid was added, and after uniform dispersion, solution A was added, and ethylene glycol was added after stirring, and the product was dried after stirring for 8-12 hours to obtain SiO2@lithium niobium titanium microspheres;

[0010] (3) Preparation of SiO2@lithium niobium titanium@SiO2 microspheres: SiO2@lithium niobium titanium microspheres were added to anhydrous ethanol, and after being evenly dispersed, ethyl orthosilicate was added; anhydrous ethanol solution of ammonia water was added dropwise to the system under stirring, and the reaction was stirred for 1 to 2 hours, and the product was separated to obtain SiO2@lithium niobium titanium@SiO2 microspheres;

[0011] (4) Preparation of SiO2@lithium niobium titanium@SiO2@LATP microspheres: LiNO3, Al(NO3)3·9H2O, and NH4H2PO4 were dissolved in deionized water, and SiO2@lithium niobium titanium@SiO2 microspheres were added. After uniform dispersion, citric acid and di(2-hydroxypropionic acid) diammonium dihydroxide titanium were added, and the reaction was stirred at 70-80°C for 12-24h to obtain SiO2@lithium niobium titanium@SiO2@LATP microspheres.

[0012] (5) primary calcination: calcining the SiO2@lithium niobium titanium@SiO2@LATP microspheres at 700-900°C for 4-6 hours under an inert atmosphere to obtain a primary calcined material;

[0013] (6) Removing the template: After the pre-sintered material is cooled, it is added into a sodium hydroxide solution, stirred and reacted at 80-90° C. for 4-6 hours, and the product is separated, washed, and dried to obtain double-shell hollow microspheres;

[0014] (7) Carbon coating: After the double-shell hollow microspheres are mixed with glucose and ball-milled, they are subjected to secondary calcination in an inert atmosphere at a calcination temperature of 900-1100° C. for 3-5 hours to obtain the double-shell lithium niobium titanium-lithium aluminum titanium phosphate composite hollow microspheres.

[0015] In the lithium-ion battery of the present invention, lithium iron manganese phosphate is used as the active material of the positive electrode, and double-shell lithium niobium titanium-lithium aluminum titanium phosphate composite hollow microspheres are used as the active material of the negative electrode. Compared with lithium iron phosphate, the lithium iron manganese phosphate of the positive electrode has a higher energy density and better low-temperature performance; compared with the ternary material, the lithium iron manganese phosphate has an olivine structure, which is more stable during charge and discharge, and has better safety and cycle stability than the ternary material.

[0016] In the process of preparing the negative electrode material of the present invention, monodispersed SiO2 microspheres are used as cores, and SiO2@lithium niobium titanium@SiO2@LATP microspheres are obtained by layer coating using a sol-gel method. After calcination, the SiO2 template layer is washed off with a sodium hydroxide solution to obtain double-shell composite hollow microspheres; glucose is then used as a carbon source to carbon-coat the surface of the double-shell hollow microspheres, and finally double-shell lithium niobium titanium-lithium aluminum titanium phosphate composite hollow microspheres with a surface coated with a carbon coating layer are obtained. In the negative electrode material prepared by the present invention, the lithium niobium titanium shell layer can make the battery have a higher specific capacity; coating the lithium aluminum titanium phosphate (LATP) shell layer outside the lithium niobium titanium shell layer can improve the ionic conductivity of the lithium niobium titanium negative electrode material, and the carbon coating layer coated outside the double-shell hollow microspheres can improve the electronic conductivity of the negative electrode material, thereby improving the battery's cycle performance at high rates. In the present application, the negative electrode material is made into a double-shell hollow microsphere. The hollow structure and the spacing between the lithium niobium titanium shell and the LATP shell can increase the specific surface area of ​​the negative electrode material, improve the permeability of the electrolyte and the contact area with the negative electrode material, provide more lithium ion transmission channels and lithium storage sites, thereby further improving its conductivity and improving the battery's rate performance.

[0017] In the process of preparing SiO2@lithium niobium titanium microspheres, stearic acid is added as a surfactant and a carbon source. On the one hand, during the primary calcination process, stearic acid is pyrolyzed to form a carbon layer coated on the surface of the lithium niobium titanium shell layer, and the carbon coating layer coated on the surface of the LLZO shell layer together improves the electronic conductivity of the negative electrode material. On the other hand, the gas generated during the pyrolysis of stearic acid can increase the pore structure in the lithium niobium titanium shell layer and the LATP shell layer, which is beneficial to the removal of the SiO2 template and the increase of the contact area between the negative electrode material and the electrolyte, thereby improving the rate performance of the battery.

[0018] Preferably, the volume ratio of tetraethyl orthosilicate, ammonia water and anhydrous ethanol added in step (1) is 1:15-25:90-100.

[0019] Preferably, in step (2), the molar ratio of LiNO3, Nb2O5 and tetrabutyl titanate is 5.2-5.4:1:5, the mass ratio of monodisperse SiO2 microspheres to tetrabutyl titanate is 1:8-10; the mass ratio of stearic acid to tetrabutyl titanate is 1:45-55; the molar ratio of citric acid to metal ions in the solution is 3-5:1, and the molar ratio of ethylene glycol to citric acid is 2-4:1.

[0020] Preferably, in step (3), the mass ratio of SiO2@lithium niobium titanium microspheres to tetraethyl orthosilicate is 1:3-5, and the volume ratio of tetraethyl orthosilicate to ammonia water is 1:5-7.

[0021] Preferably, in step (4), the molar ratio of LiNO3, Al(NO3)3·9H2O, di(2-hydroxypropionic acid) diammonium dihydroxide titanium and NH4H2PO4 is 1.4-1.6:0.4:1.6:3; the ratio of the mass of SiO2@lithium niobium titanium@SiO2 microspheres to the total mass of the metal salt is 0.3-0.5:1; and the molar ratio of citric acid to the metal atoms in the solution is 1:1-1.5.

[0022] Preferably, the concentration of the sodium hydroxide solution in step (6) is 2 to 5 mol / L.

[0023] Preferably, in step (7), the mass ratio of double-shell hollow microspheres to glucose is 1:0.15-0.25, the ball milling medium is anhydrous ethanol, and the ball milling time is 2-4 hours.

[0024] Preferably, the electrolyte includes lithium salt and carbonate organic solvent.

[0025] Preferably, the concentration of lithium salt in the electrolyte is 1-2 mol / L.

[0026] Therefore, the present invention has the following beneficial effects:

[0027] (1) Using double-shell lithium niobium titanium-lithium aluminum titanium phosphate composite hollow microspheres as the active material of the negative electrode can improve the ionic conductivity and electronic conductivity of the lithium niobium titanium negative electrode material and improve the cycle performance of the battery at high rates;

[0028] (2) Coating a carbon layer outside the lithium niobium titanium shell and the LATP shell can improve the electronic conductivity of the negative electrode material; at the same time, when stearic acid is used as a carbon source for pyrolysis, it can increase the pores in the lithium niobium titanium shell and the LATP shell, which is beneficial to increase the contact area between the negative electrode material and the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is the cycle curve of the battery in Example 1.

[0030] Figure 2 This is the cycle curve of the battery in Example 2.

[0031] Figure 3 This is the cycle curve of the battery in Example 3.

[0032] Figure 4 This is the cycle curve of the battery in Comparative Example 1.

[0033] Figure 5 This is the cycle curve of the battery in Comparative Example 2.

[0034] Figure 6 This is the cycle curve of the battery in Comparative Example 3.

[0035] Figure 7 This is the cycle curve of the battery in Comparative Example 4. DETAILED DESCRIPTION

[0036] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.

[0037] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.

[0038] Embodiment 1:

[0039] A lithium niobium titanium negative electrode-lithium manganese iron phosphate positive electrode button lithium ion battery, comprising a positive electrode, a negative electrode and an electrolyte;

[0040] The components of the electrolyte are as follows: 1 mol / L LiPF6 is dissolved in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC), and the mass ratio of EC, EMC and DMC in the mixed solvent is 1:1:1;

[0041] Positive electrode components: Active material LiMn 0.6 Fe 0.4 PO4, Super P, PVDF, the mass ratio is 93:4:3;

[0042] Negative electrode components: active material, Super P, PVDF, with a mass ratio of 95:2:3;

[0043] The active material in the negative electrode is a double-shell lithium niobium titanium-lithium aluminum titanium phosphate composite hollow microsphere, and the preparation method thereof is as follows:

[0044] (1) Preparation of monodisperse SiO2 microspheres: under stirring at 70 r / min, an anhydrous ethanol solution of tetraethyl orthosilicate was added dropwise to an anhydrous ethanol solution of ammonia water, the volume ratio of tetraethyl orthosilicate, ammonia water, and anhydrous ethanol being 1:20:96, and the reaction was continued by stirring for 1.5 h, and the product was centrifuged to obtain monodisperse SiO2 microspheres;

[0045] (2) Preparation of SiO2@lithium niobium titanium microspheres: Nb2O5 was dissolved in hydrofluoric acid, and then citric acid was added, and then ammonia water was added to adjust the pH to 5 to obtain solution A; LiNO3 and tetrabutyl titanate were added to the citric acid solution, and after dissolving, ammonia water was added to adjust the pH to 5 to obtain solution B; monodisperse SiO2 microspheres were added to solution B, and stearic acid was added, and after uniform dispersion, solution A was added, and ethylene glycol was added. After stirring for 10 hours, the product was dried to obtain SiO2@lithium niobium titanium microspheres; the molar ratio of LiNO3, Nb2O5, and tetrabutyl titanate was 5.3:1:5, and the mass ratio of monodisperse SiO2 microspheres to tetrabutyl titanate was 1:9; the mass ratio of stearic acid to tetrabutyl titanate was 1:50; the molar ratio of citric acid to metal ions in the solution was 4:1, and the molar ratio of ethylene glycol to citric acid was 3:1;

[0046] (3) Preparation of SiO2@lithium niobium titanium@SiO2 microspheres: SiO2@lithium niobium titanium microspheres were added to anhydrous ethanol, and after being evenly dispersed, tetraethyl orthosilicate was added; anhydrous ethanol solution of ammonia water was added dropwise to the system under stirring, and the reaction was stirred for 1.5 h. The product was separated to obtain SiO2@lithium niobium titanium@SiO2 microspheres; the mass ratio of SiO2@lithium niobium titanium microspheres to tetraethyl orthosilicate was 1:4, and the volume ratio of tetraethyl orthosilicate to ammonia water was 1:6;

[0047] (4) Preparation of SiO2@lithium niobium titanium@SiO2@LATP microspheres: LiNO3, Al(NO3)3·9H2O, and NH4H2PO4 were dissolved in deionized water, and SiO2@lithium niobium titanium@SiO2 microspheres were added. After uniform dispersion, citric acid and di(2-hydroxypropionic acid) diammonium titanium dihydroxide were added, and the mixture was stirred at 75°C for 18 h to obtain SiO2@lithium niobium titanium@SiO2@LATP microspheres. The molar ratio of LiNO3, Al(NO3)3·9H2O, di(2-hydroxypropionic acid) diammonium titanium dihydroxide, and NH4H2PO4 was 1.5:0.4:1.6:3. The ratio of the mass of SiO2@lithium niobium titanium@SiO2 microspheres to the total mass of metal salts was 0.4:1. The molar ratio of citric acid to metal atoms in the solution was 1:1.3.

[0048] (5) primary calcination: calcining SiO2@lithium niobium titanium@SiO2@LATP microspheres at 800°C for 5 h in an argon atmosphere to obtain a primary calcined material;

[0049] (6) Removing the template: After the pre-sintered material is cooled, it is added into a sodium hydroxide solution and reacted at 85° C. with stirring for 5 h. The product is separated, washed, and dried to obtain double-shell hollow microspheres;

[0050] (7) Carbon coating: After the double-shell hollow microspheres are mixed with glucose and ball-milled, they are subjected to secondary calcination in an argon atmosphere at a calcination temperature of 1000° C. for 4 h to obtain the double-shell lithium niobium titanium-lithium aluminum titanium phosphate composite hollow microspheres.

[0051] Embodiment 2:

[0052] A lithium niobium titanium negative electrode-lithium manganese iron phosphate positive electrode button lithium ion battery, comprising a positive electrode, a negative electrode and an electrolyte;

[0053] The components of the electrolyte are as follows: 1 mol / L LiPF6 is dissolved in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC), and the mass ratio of EC, EMC and DMC in the mixed solvent is 1:1:1;

[0054] Positive electrode components: Active material LiMn 0.6 Fe 0.4 PO4, Super P, PVDF, the mass ratio is 90:4:3;

[0055] Negative electrode components: active material, Super P, PVDF, with a mass ratio of 90:2:3;

[0056] The active material in the negative electrode is a double-shell lithium niobium titanium-lithium aluminum titanium phosphate composite hollow microsphere, and the preparation method thereof is as follows:

[0057] (1) Preparation of monodisperse SiO2 microspheres: under stirring at 60 r / min, an anhydrous ethanol solution of tetraethyl orthosilicate was added dropwise to an anhydrous ethanol solution of ammonia water, the volume ratio of tetraethyl orthosilicate, ammonia water, and anhydrous ethanol being 1:15:90, and the reaction was continued by stirring for 1 h. The product was centrifuged to obtain monodisperse SiO2 microspheres;

[0058] (2) Preparation of SiO2@lithium niobium titanium microspheres: Nb2O5 was dissolved in hydrofluoric acid, and then citric acid was added, and then ammonia water was added to adjust the pH to 4 to obtain solution A; LiNO3 and tetrabutyl titanate were added to the citric acid solution, and after dissolving, ammonia water was added to adjust the pH to 4 to obtain solution B; monodisperse SiO2 microspheres were added to solution B, and stearic acid was added, and after uniform dispersion, solution A was added, and ethylene glycol was added. After stirring for 8 hours, the product was dried to obtain SiO2@lithium niobium titanium microspheres; the molar ratio of LiNO3, Nb2O5, and tetrabutyl titanate was 5.2:1:5, and the mass ratio of monodisperse SiO2 microspheres to tetrabutyl titanate was 1:8; the mass ratio of stearic acid to tetrabutyl titanate was 1:55; the molar ratio of citric acid to metal ions in the solution was 3:1, and the molar ratio of ethylene glycol to citric acid was 4:1;

[0059] (3) Preparation of SiO2@lithium niobium titanium@SiO2 microspheres: SiO2@lithium niobium titanium microspheres were added to anhydrous ethanol, and after being evenly dispersed, tetraethyl orthosilicate was added; anhydrous ethanol solution of ammonia water was added dropwise to the system under stirring, and the reaction was stirred for 1 hour, and the product was separated to obtain SiO2@lithium niobium titanium@SiO2 microspheres; the mass ratio of SiO2@lithium niobium titanium microspheres to tetraethyl orthosilicate was 1:3, and the volume ratio of tetraethyl orthosilicate to ammonia water was 1:5;

[0060] (4) Preparation of SiO2@lithium niobium titanium@SiO2@LATP microspheres: LiNO3, Al(NO3)3·9H2O, and NH4H2PO4 were dissolved in deionized water, and SiO2@lithium niobium titanium@SiO2 microspheres were added. After uniform dispersion, citric acid and di(2-hydroxypropionic acid) diammonium titanium dihydroxide were added. The mixture was stirred and reacted at 70°C for 24 hours to obtain SiO2@lithium niobium titanium@SiO2@LATP microspheres. The molar ratio of LiNO3, Al(NO3)3·9H2O, di(2-hydroxypropionic acid) diammonium titanium dihydroxide, and NH4H2PO4 was 1.4:0.4:1.6:3. The ratio of the mass of SiO2@lithium niobium titanium@SiO2 microspheres to the total mass of metal salts was 0.3:1. The molar ratio of citric acid to metal atoms in the solution was 1:1.

[0061] (5) primary calcination: calcining SiO2@lithium niobium titanium@SiO2@LATP microspheres at 700°C for 6 h in an argon atmosphere to obtain a primary calcined material;

[0062] (6) Removing the template: After the pre-sintered material is cooled, it is added into a sodium hydroxide solution and reacted at 80° C. with stirring for 6 h. The product is separated, washed, and dried to obtain double-shell hollow microspheres;

[0063] (7) Carbon coating: After the double-shell hollow microspheres are mixed with glucose and ball-milled, they are subjected to secondary calcination in an argon atmosphere at a calcination temperature of 1100° C. for 3 h to obtain the double-shell lithium niobium titanium-lithium aluminum titanium phosphate composite hollow microspheres.

[0064] Embodiment 3:

[0065] A lithium niobium titanium negative electrode-lithium manganese iron phosphate positive electrode button lithium ion battery, comprising a positive electrode, a negative electrode and an electrolyte;

[0066] The components of the electrolyte are as follows: 2 mol / L LiPF6 is dissolved in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC), and the mass ratio of EC, EMC and DMC in the mixed solvent is 1:1:1;

[0067] Positive electrode components: Active material LiMn 0.6 Fe 0.4PO4, Super P, PVDF, the mass ratio is 95:4:3;

[0068] Negative electrode components: active material, Super P, PVDF, with a mass ratio of 95:2:3;

[0069] The active material in the negative electrode is a double-shell lithium niobium titanium-lithium aluminum titanium phosphate composite hollow microsphere, and the preparation method thereof is as follows:

[0070] (1) Preparation of monodisperse SiO2 microspheres: under stirring at 80 r / min, an anhydrous ethanol solution of tetraethyl orthosilicate was added dropwise to an anhydrous ethanol solution of ammonia water, the volume ratio of tetraethyl orthosilicate, ammonia water, and anhydrous ethanol being 1:25:100, the stirring reaction was continued for 2 h, and the product was centrifuged to obtain monodisperse SiO2 microspheres;

[0071] (2) Preparation of SiO2@lithium niobium titanium microspheres: Nb2O5 was dissolved in hydrofluoric acid, and then citric acid was added, and then ammonia water was added to adjust the pH to 6 to obtain solution A; LiNO3 and tetrabutyl titanate were added to the citric acid solution, and after dissolving, ammonia water was added to adjust the pH to 6 to obtain solution B; monodisperse SiO2 microspheres were added to solution B, and stearic acid was added, and after uniform dispersion, solution A was added, and ethylene glycol was added. After stirring for 8 hours, the product was dried to obtain SiO2@lithium niobium titanium microspheres; the molar ratio of LiNO3, Nb2O5, and tetrabutyl titanate was 5.4:1:5, and the mass ratio of monodisperse SiO2 microspheres to tetrabutyl titanate was 1:10; the mass ratio of stearic acid to tetrabutyl titanate was 1:45; the molar ratio of citric acid to metal ions in the solution was 5:1, and the molar ratio of ethylene glycol to citric acid was 2:1;

[0072] (3) Preparation of SiO2@lithium niobium titanium@SiO2 microspheres: SiO2@lithium niobium titanium microspheres were added to anhydrous ethanol, and after being evenly dispersed, tetraethyl orthosilicate was added; anhydrous ethanol solution of ammonia water was added dropwise to the system under stirring, and the reaction was stirred for 1 hour, and the product was separated to obtain SiO2@lithium niobium titanium@SiO2 microspheres; the mass ratio of SiO2@lithium niobium titanium microspheres to tetraethyl orthosilicate was 1:5, and the volume ratio of tetraethyl orthosilicate to ammonia water was 1:7;

[0073] (4) Preparation of SiO2@lithium niobium titanium@SiO2@LATP microspheres: LiNO3, Al(NO3)3·9H2O, and NH4H2PO4 were dissolved in deionized water, and SiO2@lithium niobium titanium@SiO2 microspheres were added. After uniform dispersion, citric acid and di(2-hydroxypropionic acid) diammonium titanium dihydroxide were added. The mixture was stirred at 80°C for 12 h to obtain SiO2@lithium niobium titanium@SiO2@LATP microspheres. The molar ratio of LiNO3, Al(NO3)3·9H2O, di(2-hydroxypropionic acid) diammonium titanium dihydroxide, and NH4H2PO4 was 1.6:0.4:1.6:3. The ratio of the mass of SiO2@lithium niobium titanium@SiO2 microspheres to the total mass of metal salts was 0.5:1. The molar ratio of citric acid to metal atoms in the solution was 1:1.5.

[0074] (5) primary calcination: calcining SiO2@lithium niobium titanium@SiO2@LATP microspheres at 900°C for 4 h in an argon atmosphere to obtain a primary calcined material;

[0075] (6) Removing the template: After the pre-sintered material is cooled, it is added into a sodium hydroxide solution and stirred at 90° C. for 4 h. The product is separated, washed and dried to obtain double-shell hollow microspheres;

[0076] (7) Carbon coating: After the double-shell hollow microspheres are mixed with glucose and ball-milled, they are subjected to secondary calcination in an argon atmosphere at a calcination temperature of 900° C. for 5 h to obtain the double-shell lithium niobium titanium-lithium aluminum titanium phosphate composite hollow microspheres.

[0077] Comparative Example 1 (without LATP layer):

[0078] In Comparative Example 1, the negative electrode active material is lithium niobium titanium hollow microspheres, and the preparation method thereof is as follows:

[0079] (1) Preparation of monodisperse SiO2 microspheres: under stirring at 70 r / min, an anhydrous ethanol solution of tetraethyl orthosilicate was added dropwise to an anhydrous ethanol solution of ammonia water, the volume ratio of tetraethyl orthosilicate, ammonia water, and anhydrous ethanol being 1:20:96, and the reaction was continued by stirring for 1.5 h, and the product was centrifuged to obtain monodisperse SiO2 microspheres;

[0080] (2) Preparation of SiO2@lithium niobium titanium microspheres: Nb2O5 was dissolved in hydrofluoric acid, and then citric acid was added, and then ammonia water was added to adjust the pH to 5 to obtain solution A; LiNO3 and tetrabutyl titanate were added to the citric acid solution, and after dissolving, ammonia water was added to adjust the pH to 5 to obtain solution B; monodisperse SiO2 microspheres were added to solution B, and stearic acid was added, and after uniform dispersion, solution A was added, and ethylene glycol was added. After stirring for 10 hours, the product was dried to obtain SiO2@lithium niobium titanium microspheres; the molar ratio of LiNO3, Nb2O5, and tetrabutyl titanate was 5.3:1:5, and the mass ratio of monodisperse SiO2 microspheres to tetrabutyl titanate was 1:9; the mass ratio of stearic acid to tetrabutyl titanate was 1:50; the molar ratio of citric acid to metal ions in the solution was 4:1, and the molar ratio of ethylene glycol to citric acid was 3:1;

[0081] (3) primary calcination: calcining SiO2@lithium niobium titanium microspheres at 800°C for 5 h in an argon atmosphere to obtain a primary calcined material;

[0082] (4) Removing the template: After cooling the primary calcined material, add it into a sodium hydroxide solution, stir and react at 85° C. for 5 h, separate, wash and dry the product to obtain double-shell hollow microspheres;

[0083] (5) Carbon coating: After the double-shell hollow microspheres are mixed with glucose and ball-milled, they are subjected to secondary calcination in an argon atmosphere at a calcination temperature of 1000° C. for 4 h to obtain the double-shell lithium niobium titanium-lithium aluminum titanium phosphate composite hollow microspheres;

[0084] The rest are the same as in Example 1.

[0085] Comparative Example 2 (no carbon coating layer):

[0086] In Comparative Example 2, the preparation method of the negative electrode active material is:

[0087] (1) Preparation of monodisperse SiO2 microspheres: under stirring at 70 r / min, an anhydrous ethanol solution of tetraethyl orthosilicate was added dropwise to an anhydrous ethanol solution of ammonia water, the volume ratio of tetraethyl orthosilicate, ammonia water, and anhydrous ethanol being 1:20:96, and the reaction was continued by stirring for 1.5 h, and the product was centrifuged to obtain monodisperse SiO2 microspheres;

[0088] (2) Preparation of SiO2@lithium niobium titanium microspheres: Nb2O5 was dissolved in hydrofluoric acid, and then citric acid was added, and then ammonia water was added to adjust the pH to 5 to obtain solution A; LiNO3 and tetrabutyl titanate were added to the citric acid solution, and after dissolving, ammonia water was added to adjust the pH to 5 to obtain solution B; monodisperse SiO2 microspheres were added to solution B, and stearic acid was added, and after uniform dispersion, solution A was added, and ethylene glycol was added. After stirring for 10 hours, the product was dried to obtain SiO2@lithium niobium titanium microspheres; the molar ratio of LiNO3, Nb2O5, and tetrabutyl titanate was 5.3:1:5, and the mass ratio of monodisperse SiO2 microspheres to tetrabutyl titanate was 1:9; the mass ratio of stearic acid to tetrabutyl titanate was 1:50; the molar ratio of citric acid to metal ions in the solution was 4:1, and the molar ratio of ethylene glycol to citric acid was 3:1;

[0089] (3) Preparation of SiO2@lithium niobium titanium@SiO2 microspheres: SiO2@lithium niobium titanium microspheres were added to anhydrous ethanol, and after being evenly dispersed, tetraethyl orthosilicate was added; anhydrous ethanol solution of ammonia water was added dropwise to the system under stirring, and the reaction was stirred for 1.5 h. The product was separated to obtain SiO2@lithium niobium titanium@SiO2 microspheres; the mass ratio of SiO2@lithium niobium titanium microspheres to tetraethyl orthosilicate was 1:4, and the volume ratio of tetraethyl orthosilicate to ammonia water was 1:6;

[0090] (4) Preparation of SiO2@lithium niobium titanium@SiO2@LATP microspheres: LiNO3, Al(NO3)3·9H2O, and NH4H2PO4 were dissolved in deionized water, and SiO2@lithium niobium titanium@SiO2 microspheres were added. After uniform dispersion, citric acid and di(2-hydroxypropionic acid) diammonium titanium dihydroxide were added, and the mixture was stirred at 75°C for 18 h to obtain SiO2@lithium niobium titanium@SiO2@LATP microspheres. The molar ratio of LiNO3, Al(NO3)3·9H2O, di(2-hydroxypropionic acid) diammonium titanium dihydroxide, and NH4H2PO4 was 1.5:0.4:1.6:3. The ratio of the mass of SiO2@lithium niobium titanium@SiO2 microspheres to the total mass of metal salts was 0.4:1. The molar ratio of citric acid to metal atoms in the solution was 1:1.3.

[0091] (5) primary calcination: calcining the SiO2@lithium niobium titanium@SiO2@LATP microspheres at 800°C for 5 h and then at 1000°C for 4 h in an argon atmosphere to obtain a primary calcined material;

[0092] (6) Removing the template: cooling the pre-sintered material, adding it to a sodium hydroxide solution, stirring and reacting at 85° C. for 5 h, separating, washing, and drying the product to obtain the double-shell lithium niobium titanium-lithium aluminum titanium phosphate composite hollow microspheres;

[0093] The rest are the same as in Example 1.

[0094] Comparative Example 3 (without hollow structure):

[0095] In Comparative Example 3, the active material of the negative electrode is a lithium niobium titanium-lithium aluminum titanium phosphate composite, and the preparation method thereof is as follows:

[0096] (1) Preparation of lithium niobium titanium: Nb2O5 is dissolved in hydrofluoric acid, and then citric acid is added, and then ammonia water is added to adjust the pH to 5 to obtain solution A; LiNO3 and tetrabutyl titanate are added to the citric acid solution, and after dissolving, ammonia water is added to adjust the pH to 5 to obtain solution B; stearic acid is added to solution B, and after stirring and dissolving, solution A is added, and after stirring evenly, ethylene glycol is added. After stirring and reacting for 10 hours, the product is dried to obtain lithium niobium titanium; the molar ratio of LiNO3, Nb2O5, and tetrabutyl titanate is 5.3:1:5; the mass ratio of stearic acid to tetrabutyl titanate is 1:50; the molar ratio of citric acid to metal ions in the solution is 4:1, and the molar ratio of ethylene glycol to citric acid is 3:1;

[0097] (2) Preparation of lithium niobium titanium @LATP: LiNO3, Al(NO3)3·9H2O, and NH4H2PO4 were dissolved in deionized water, and lithium niobium titanium was added. After being evenly dispersed, citric acid and di(2-hydroxypropionic acid) diammonium titanium dihydroxide were added, and the mixture was stirred and reacted at 75°C for 18 hours to obtain lithium niobium titanium @LATP; the molar ratio of LiNO3, Al(NO3)3·9H2O, di(2-hydroxypropionic acid) diammonium titanium dihydroxide, and NH4H2PO4 was 1.5:0.4:1.6:3; the ratio of the mass of lithium niobium titanium to the total mass of the metal salt was 0.4:1; the molar ratio of citric acid to the metal atoms in the solution was 1:1.3;

[0098] (3) primary calcination: calcining lithium niobium titanium @LATP at 800°C for 5 h in an argon atmosphere to obtain a primary calcined material;

[0099] (4) Carbon coating: After the double-shell hollow microspheres were mixed with glucose and ball-milled, they were calcined twice in an argon atmosphere at a temperature of 1000° C. for 4 h to obtain a lithium niobium titanium-lithium aluminum titanium phosphate composite;

[0100] The rest are the same as in Example 1.

[0101] Comparative Example 4 (no space between two shell layers):

[0102] In Comparative Example 4, the preparation method of the negative electrode active material is:

[0103] (1) Preparation of monodisperse SiO2 microspheres: under stirring at 70 r / min, an anhydrous ethanol solution of tetraethyl orthosilicate was added dropwise to an anhydrous ethanol solution of ammonia water, the volume ratio of tetraethyl orthosilicate, ammonia water, and anhydrous ethanol being 1:20:96, and the reaction was continued by stirring for 1.5 h, and the product was centrifuged to obtain monodisperse SiO2 microspheres;

[0104] (2) Preparation of SiO2@lithium niobium titanium microspheres: Nb2O5 was dissolved in hydrofluoric acid, and then citric acid was added, and then ammonia water was added to adjust the pH to 5 to obtain solution A; LiNO3 and tetrabutyl titanate were added to the citric acid solution, and after dissolving, ammonia water was added to adjust the pH to 5 to obtain solution B; monodisperse SiO2 microspheres were added to solution B, and stearic acid was added, and after uniform dispersion, solution A was added, and ethylene glycol was added. After stirring for 10 hours, the product was dried to obtain SiO2@lithium niobium titanium microspheres; the molar ratio of LiNO3, Nb2O5, and tetrabutyl titanate was 5.3:1:5, and the mass ratio of monodisperse SiO2 microspheres to tetrabutyl titanate was 1:9; the mass ratio of stearic acid to tetrabutyl titanate was 1:50; the molar ratio of citric acid to metal ions in the solution was 4:1, and the molar ratio of ethylene glycol to citric acid was 3:1;

[0105] (3) Preparation of SiO2@lithium niobium titanium@LATP microspheres: LiNO3, Al(NO3)3·9H2O, and NH4H2PO4 were dissolved in deionized water, and SiO2@lithium niobium titanium microspheres were added. After uniform dispersion, citric acid and di(2-hydroxypropionic acid) diammonium titanium dihydroxide were added, and the mixture was stirred at 75°C for 18 h to obtain SiO2@lithium niobium titanium@LATP microspheres. The molar ratio of LiNO3, Al(NO3)3·9H2O, di(2-hydroxypropionic acid) diammonium titanium dihydroxide, and NH4H2PO4 was 1.5:0.4:1.6:3. The ratio of the mass of SiO2@lithium niobium titanium microspheres to the total mass of metal salts was 0.4:1. The molar ratio of citric acid to metal atoms in the solution was 1:1.3.

[0106] (4) primary calcination: calcining SiO2@lithium niobium titanium@LATP microspheres at 800°C for 5 h in an argon atmosphere to obtain a primary calcined material;

[0107] (5) Removing the template: After the pre-sintered material is cooled, it is added into a sodium hydroxide solution and reacted at 85° C. with stirring for 5 h. The product is separated, washed, and dried to obtain double-shell hollow microspheres;

[0108] (6) Carbon coating: After the double-shell hollow microspheres are mixed with glucose and ball-milled, they are subjected to secondary calcination in an argon atmosphere at a calcination temperature of 1000° C. for 4 h to obtain the double-shell lithium niobium titanium-lithium aluminum titanium phosphate composite hollow microspheres.

[0109] Comparative Example 5 (stearic acid is not added in step (2)):

[0110] In step (2) of comparative example 5, stearic acid was not added during the preparation of SiO2@lithium niobium titanium microspheres, and the rest was the same as in example 1.

[0111] The performance of the lithium ion batteries in the above examples and comparative examples was tested, and their discharge capacity, rate discharge and cycle life were evaluated in the range of 1.5 to 2.8 V. The results are shown in Tables 1 and Figures 1 to 7 as shown in .

[0112] Table 1: Lithium niobium titanium battery performance test results.

[0113]

[0114] From Table 1 and Figures 1 to 7 It can be seen that the negative electrode active material of Examples 1 to 3 adopts the double-shell lithium niobium titanium-lithium aluminum titanium phosphate composite hollow microspheres prepared by the present invention, and the battery has good rate performance, high initial capacity, and high capacity retention rate during high rate charge and discharge.

[0115] In the negative electrode active material in Comparative Example 1, the carbon coating layer is directly coated on the surface of the lithium niobium titanium hollow microspheres without setting the LATP layer. The ionic conductivity of the material decreases, resulting in a decrease in the rate performance of the battery compared with Example 1, and a decrease in the cycle performance at high rates.

[0116] In the negative electrode active material in Comparative Example 2, the carbon coating layer is not coated on the surface of the material, and the electronic conductivity of the material is low, which also leads to a decrease in the rate performance and cycle performance of the battery at a high rate.

[0117] The negative electrode active material in Comparative Example 3 is not made into hollow microspheres. In the negative electrode active material of Comparative Example 4, LATP is directly coated on the surface of lithium niobium titanium hollow microspheres. There is no gap between LATP and lithium niobium titanium. The cycle performance of the battery at high rate is reduced compared with that in Example 1.

[0118] In Comparative Example 5, stearic acid is not added during the SiO2@lithium niobium titanium microsphere process, and there is no carbon coating on the surface of the lithium niobium titanium shell layer, and the electronic conductivity of the negative electrode active material decreases; and the porosity of the lithium niobium titanium shell layer and the LATP shell layer also decreases, resulting in a decrease in the rate performance and cycle performance of the battery.

Claims

1. A lithium niobium titanium negative electrode-lithium manganese iron phosphate positive electrode lithium ion battery, characterized in that: It includes a positive electrode, a negative electrode and an electrolyte; the active material in the positive electrode is lithium manganese iron phosphate; The active material in the negative electrode is a double-shell lithium niobium titanium-lithium aluminum titanium phosphate composite hollow microsphere, and the preparation method thereof comprises the following steps: (1) Preparation of monodisperse SiO2 microspheres: under stirring, add anhydrous ethanol solution of ethyl orthosilicate dropwise into anhydrous ethanol solution of ammonia water, stir and react for 1-2 hours, and separate the product to obtain monodisperse SiO2 microspheres; (2) Preparation of SiO2@lithium niobium titanium microspheres: Nb2O5 was dissolved in hydrofluoric acid, and then citric acid was added, and then ammonia water was added to adjust the pH to 4-6 to obtain solution A; LiNO3 and tetrabutyl titanate were added to the citric acid solution, and after dissolving, ammonia water was added to adjust the pH to 4-6 to obtain solution B; monodisperse SiO2 microspheres were added to solution B, and stearic acid was added. After uniform dispersion, solution A was added, and ethylene glycol was added after stirring. After stirring for 8-12 hours, the product was dried to obtain SiO2@lithium niobium titanium microspheres; (3) Preparation of SiO2@lithium niobium titanium@SiO2 microspheres: Add SiO2@lithium niobium titanium microspheres into anhydrous ethanol, disperse them evenly, and then add ethyl orthosilicate; add anhydrous ethanol solution of ammonia water dropwise into the system under stirring, stir and react for 1-2 hours, and separate the product to obtain SiO2@lithium niobium titanium@SiO2 microspheres; (4) Preparation of SiO2@lithium niobium titanium@SiO2@LATP microspheres: Dissolve LiNO3, Al(NO3)3•9H2O, and NH4H2PO4 in deionized water, and add SiO2@lithium niobium titanium@SiO2 microspheres. After uniform dispersion, add citric acid and di(2-hydroxypropionic acid) diammonium dihydroxide titanium. Stir the reaction at 70-80°C for 12-24h to obtain SiO2@lithium niobium titanium@SiO2@LATP microspheres. (5) Primary calcination: calcining the SiO2@lithium niobium titanium@SiO2@LATP microspheres at 700-900°C for 4-6 hours under an inert atmosphere to obtain a primary calcined material; (6) Removing the template: After the pre-sintered material is cooled, it is added into a sodium hydroxide solution and stirred at 80-90°C for 4-6 hours. The product is separated, washed and dried to obtain double-shell hollow microspheres. (7) Carbon coating: After the double-shell hollow microspheres are mixed with glucose and ball-milled, they are subjected to secondary calcination in an inert atmosphere at a calcination temperature of 900-1100° C. for a calcination time of 3-5 h to obtain the double-shell lithium niobium titanium-lithium aluminum titanium phosphate composite hollow microspheres.

2. A lithium niobium titanium negative electrode-lithium manganese iron phosphate positive electrode lithium ion battery according to claim 1, characterized in that: The volume ratio of ethyl orthosilicate, ammonia water and anhydrous ethanol added in step (1) is 1:15-25:90-100.

3. A lithium niobium titanium negative electrode-lithium manganese iron phosphate positive electrode lithium ion battery according to claim 1, characterized in that: In step (2), the molar ratio of LiNO3, Nb2O5 and tetrabutyl titanate is 5.2-5.4:1:5, the mass ratio of monodisperse SiO2 microspheres to tetrabutyl titanate is 1:8-10; the mass ratio of stearic acid to tetrabutyl titanate is 1:45-55; The molar ratio of citric acid to metal ions in the solution is 3-5:1, and the molar ratio of ethylene glycol to citric acid is 2-4:

1.

4. A lithium niobium titanium negative electrode-lithium manganese iron phosphate positive electrode lithium ion battery according to claim 1, characterized in that: In step (3), the mass ratio of SiO2@lithium niobium titanium microspheres to tetraethyl orthosilicate is 1:3-5, and the volume ratio of tetraethyl orthosilicate to ammonia water is 1:5-7.

5. A lithium niobium titanium negative electrode-lithium manganese iron phosphate positive electrode lithium ion battery according to claim 1, characterized in that: In step (4), the molar ratio of LiNO3, Al(NO3)3•9H2O, di(2-hydroxypropionic acid) diammonium dihydroxide titanium and NH4H2PO4 is 1.4~1.6:0.4:1.6:3; the ratio of the mass of SiO2@lithium niobium titanium@SiO2 microspheres to the total mass of metal salts is 0.3~0.5:1; and the molar ratio of citric acid to metal atoms in the solution is 1:1~1.

5.

6. A lithium niobium titanium negative electrode-lithium manganese iron phosphate positive electrode lithium ion battery according to claim 1, characterized in that: The concentration of the sodium hydroxide solution in step (6) is 2-5 mol / L.

7. A lithium niobium titanium negative electrode-lithium manganese iron phosphate positive electrode lithium ion battery according to claim 1, characterized in that: In step (7), the mass ratio of double-shell hollow microspheres to glucose is 1:0.15-0.25, the ball milling medium is anhydrous ethanol, and the ball milling time is 2-4 hours.

8. A lithium niobium titanium negative electrode-lithium manganese iron phosphate positive electrode lithium ion battery according to claim 1, characterized in that: The electrolyte includes lithium salt and carbonate organic solvent.

9. A lithium niobium titanium negative electrode-lithium manganese iron phosphate positive electrode lithium ion battery according to claim 8, characterized in that: The concentration of lithium salt in the electrolyte is 1-2 mol / L.

Citation Information

Patent Citations

  • Negative electrode active material, its preparation method, and lithium-ion secondary batteries prepared using the negative electrode active material

    CN102299311A

  • A preparation method of conductive polymer coated lithium titanate anode material

    CN109216676A